Ways to implement a health protective educational environment in higher education - Mykytyuk O.M (Kharkov National Pedagogical University, 2012)
The features of organization and creation of health protective educational environment are exposed in higher institute. They foresee creation of the special terms for realization structurally of functional model of organization of students' healthy way of life. A model plugs in itself pedagogical, organizational, material and technical, sanitary-hygenic, informatively-methodical, skilled and financial economic terms. A questionnaire is conducted 95 students of 1-3 courses. It is set that the level of factors of risk for the health of students is high enough: prevalence of smoking is 47%, swizzles use more than 20%. It is discovered that the number of students with active physical activity makes not more than 45%. Most students consider that for the health they are responsible, ready and want to get information on forming of healthy way of life. Principles of organization of health protective behave to the features of organization of health protective of educational environment, nature protective, valeological, sequence, integration, pedagogical support, flexibility.